First and second-generation commercial banks in Bangladesh: A comparative financial analysis - Akber, S. M.; Mahjabeen, Meherun Nesa; Jumman, Oporbo Hossain (goodwood publishing, 2024)
Purpose: This study assesses the overall performance of commercial banks in Bangladesh by classifying them into first- and second-generation groups. Research Methodology: The investigation encompassed secondary data from 2016 to 2020, along with a meticulous examination of the ratios of ten banks during that timeframe. Standard software such as the Microsoft Office package was utilized for conducting horizontal, vertical, and rational analyses. Return on assets (ROA), return on equity (ROE), and net profit margins are the primary metrics used to assess overall performance. Results: Research indicates that the first generation excels in certain instances, while the second generation performs at its peak capacity in other cases. Therefore, a comprehensive outcome exists. Implications: These indicators offer a concise and influential message to all stakeholders that may shape their decision-making process. Limitations: It may be beneficial to consider a longer timeframe and gather insights from interviews with industry professionals for subsequent studies. Other factors to consider include customer insights, industry conditions, the nation's economy, monetary policy, and the global trade situation. Novelty: This study focuses on the influence of employee retention on organizational performance in a service-oriented government institution.